Analisis Faktor-Faktor yang Mempengaruhi Ketepatan Penyampaian Pelaporan Keuangan pada PT Bank Sulselbar Cabang Makassar - Sudirman, Sudirman; Pratama, Ghalif; Syah, Sri Rahayu; Syafrimasyah, Syafrimasyah; Tawakkal, Ujianti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The purpose of this study is to ascertain how the accuracy of financial reports submitted to the PT Bank Sulselbar Makassar Branch is affected by factors such as profitability, leverage, liquidity, and firm age. The study employed a quantitative methodology that employed multiple linear regression analysis, processed by SPSS version 26.0, to examine the relationship between the variables of profitability, leverage, liquidity, and firm age and the timely filing of financial reports submitted during the previous two years. Purposive sampling was used to choose the study's sample. Looking at the profitability variable (X1), which has a t value of -0.849 and a significance value of 0.403, which is greater than 0.05, the research results demonstrate that company profitability has no effect on the timeliness of filing financial reports. The precision with which corporate financial reports are submitted is unaffected by financial leverage. In accordance with the linear regression results, we can see that the Leverage variable (X2) has a t value of -0.296 and a significance value of 0.770 which is greater than 0.05. Company liquidity has no effect on the accuracy of submitting company financial reports. This is in accordance with the results of the linear regression in the table above, so we can see that the Liquidity variable (X3) has a t value of 0.915 and a significance value of 0.368 which is greater than 0.05. Company age has no effect on accuracy of delivery. The results of the linear regression in the above table are consistent with the financial report for this company, and as a result, we can observe that the variable Company Age (X4) has a t value of -1.126 and a significance value of 0.270, both of which are greater than 0.05. Overall, the independent variable simultaneously has no effect on the dependent variable based on The F value of the research model is 0.524 with a significance level of0. 719. The significance value is above 0.05.